Submental Microneedles of Botulinum Toxin A for Double Chin After Neck Injection - Shuai Qiang, MD; Jie Long, MD; Han Chen, MD; Songjie Li, MD; Xin Dan, MD; Yang Li, MD; Xing Fan, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Neck injections of botulinum toxin A (BTX-A) are an effective, minimally invasive approach to improve lower face sagging, especially in Asian populations. However, cases of worsened “double chin” have been observed postinjection, likely due to the platysma muscle type and limited anterior neck injection range, which may result in compensatory platysma contraction. Five female patients who developed aggravated double chin after BTX-A injections in the lower jaw and neck were treated with microneedle BTX-A injections (10–20 U in 3–4 rows with 0.5–1 cm between points). Effective submental lifting and double chin improvement were observed within 5–10 days, with no reports of voice changes or dysphagia. This microneedle BTX-A injection technique provides a safe, effective solution for enhancing the anterior neck region and can serve as an important adjunct to lower face antiaging treatments.